Discovery of a Cryptic Intermediate in Late Steps of Mithramycin Biosynthesis. Issue 2 (27th November 2019) - Wheeler, Ryan; Yu, Xia; Hou, Caixia; Mitra, Prithiba; Chen, Jhong‐Min; Herkules, Frank; Ivanov, Dmitri N.; Tsodikov, Oleg V.; Rohr, Jürgen
Abstract: MtmOIV and MtmW catalyze the final two reactions in the mithramycin (MTM) biosynthetic pathway, the Baeyer–Villiger opening of the fourth ring of premithramycin B (PMB), creating the C3 pentyl side chain, strictly followed by reduction of the distal keto group on the new side chain. Unexpectedly this results in a C2 stereoisomer of mithramycin, iso‐mithramycin (iso‐MTM). Iso‐MTM undergoes a non‐enzymatic isomerization to MTM catalyzed by Mg 2+ ions. Crystal structures of MtmW and its complexes with co‐substrate NADPH and PEG, suggest a catalytic mechanism of MtmW. The structures also show that a tetrameric assembly of this enzyme strikingly resembles the ring‐shaped β subunit of a vertebrate ion channel. We show that MtmW and MtmOIV form a complex in the presence of PMB and NADPH, presumably to hand over the unstable MtmOIV product to MtmW, yielding iso‐MTM, as a potential self‐resistance mechanism against MTM toxicity. Abstract : MtmOIV and MtmW catalyze the final two reactions in the mithramycin biosynthetic pathway, the Baeyer–Villiger opening of the fourth ring of premithramycin B, creating the C3 pentyl side chain, followed by reduction of the distal keto group on the new side chain. Unexpectedly this results in a C2 stereoisomer of mithramycin, iso‐mithramycin (iso‐MTM).